Variation and relationship of quality and near infrared spectral characteristics of cotton fibers collected from multi-location field performance trials. Issue 14 (September 2015) - Liu, Yongliang; Todd Campbell, B; Delhom, Chris; Martin, Vikki
Standardized instrument for testing of cotton (SITC) and advanced fiber information system (AFIS) measurements are increasingly being utilized as primary and routine means of acquiring fiber quality data by cotton breeders and fiber processors. A significant amount of information regarding fiber and yarn qualities is present, but little information exists about the compositional and chemical structure difference of cotton fibers harvested at different locations. Such information could prove useful in attempts to understand the variety selection of cotton cultivars. The purpose of this study was to characterize the fiber SITC and AFIS quality and also yarn skein strength of cottons harvested from various locations, and also to unravel the near infrared (NIR) spectral response to these differential environments. Moderate positive or negative relationships among fiber properties were observed. However, these relationships varied across experimental locations and years. Further, the analysis of variance tests indicated substantial variations among genotypes for most fiber properties, but less detectable variation among genotypes for yarn tenacity. Interestingly, principal component analysis of NIR spectra enhanced the similarity or dissimilarity of cotton fibers harvested at differing locations, implying the feasibility of the NIR technique for site selection in future cotton variety trials.